Effect of temperature, strain rate and particle size on the yield stresses and post-yield strain softening of PMMA and its composites. (20th April 2015) - Jancar, Josef; Hoy, Robert S.; Jancarova, Ema; Zidek, Jan
Abstract: The extent of strain softening controls strain localization and governs the character of the post-yield response of polymer glasses. In order to understand how solid particles affect strain softening in a common glassy polymer, we investigate the composition dependence of the upper ( σ y ), lower ( σ fl ), and rejuvenated ( σ yr ) yield stresses of neat PMMA as well as glass microparticle (MP) and silica nanoparticle (NP) filled PMMA composites. All yield stresses increase with the filler volume fraction v f, as expected; the extent of this enhancement increases with T, and is uniformly larger for NP- than for MP-filled systems. This trend cannot be interpreted using simple volume-replacement models; we interpret their breakdown as arising from NP-imposed alteration of segment-scale packing and dynamics at the filler-matrix interface. Furthermore, they vary qualitatively differently with temperature and strain rate, leading to disparate responses of two measures of strain softening ( Δσ fl  =  σ y −σ fl and Δσ yr  =  σ y −σ yr ). We analyze these results in terms of recent microscopic and constitutive models. The strain rate dependence of Δσ fl agrees well with predictions of the Chen-Schweizer PNLE model, while poorer agreement is found for temperature dependence. Finally, we extend the recently developed "three-region" picture of strain softening (van Breemen LCA, Engels TAP, Klompen ETJ, Senden DJA, Govaert LE, J Polym Sci Polym Phys 2012, 50, 1757) to composite systems. Our results should lead to an improved understanding of the factors controlling plastic deformation of polymer composites. Graphical abstract: Highlights: Fillers alter the character of the matrix dependent on particle size, spatial arrangement and composite preparation protocol. Yield stress of the surface immobilized layer exhibits weaker T dependence compared to matrix bulk. NPs reduce the extent of strain softening more effectively than MPs.